Al-Subki: A biographical history and achievements - Babu Sahib, Hikmatullah; Yaacob, Asiah (s.n, 2012)
Taj al-Din al-Subki (728 A.H - 771 A.H) occupies an important position in the analysis of 8th century Muslim scholarship. His contributions to Islamic studies are still held in esteem by men of erudition. This article attempts to capture the details of his biography through the study of history and his achievements